Factors Contributing To Job Dissatisfaction And Its Effect On Employee Relationship Management (Erm): The Case Of Managing Employee Turnover In Medicins Sdn. Bhd - Mohammad, Ismeth Yazmin; Priyah, Wilson (2014)
MEDICINS Sdn. Bhd. (MEDICINS) is facing unfavourable employee turnover; an increase of 1.76% from 2012 to 2013. The employee turnover rate in 2013 was 12.64% and in 2012 it was 10.88%. This situation indicates that the organization is loosing talents at a fast pace. MEDICINS formed a cross functional project team. TARI project is short for Turnover, Attendance, and Retention Initiative. TARI project seeks to identify the factors leading to employee turnover and to introduce effective and cost efficient retention strategies. The objective of this paper is to outline the case study undertaken to identify the main reasons of job dissatisfaction among employees of MEDICINS in an effort to reduce its employee turnover.